Axiokebuita Pocklington & Fournier 1987 - Blake, James A. (Zenodo, 2023)
Genus Axiokebuita Pocklington & Fournier, 1987 Type species : Axiokebuita millsi Pocklington & Fournier, 1987, by monotypy. Diagnosis . (Emended after Blake, 2020): Body elongate, with segments similar throughout, but some species with a fusiform shape; segments with one to four annulated rings composed of small, inconspicuous elevated pads, best developed on middle and posterior segments; venter with weakly developed median ridge. Prostomium triangular to pentagonal, truncate on anterior margin with long, subterminal ciliated lateral horns; eyes absent, nuchal organs in narrow grooves on posterior part. Peristomium a single, complete ring, weakly incised dorsally, divided into upper and lower lips of mouth ventrally; formed from large expanded lobes; unique paired ciliated “neck organs” present posterior to lower lip of mouth. Parapodia narrow ventral postsetal cirrus. Branchiae absent. Setae all capillaries, furcate and spinous setae absent; long, natatory-like setae present or absent. Pygidium reduced, short anal cirri present or absent; or with two pad-like lobes covered with papillae or papillae absent. Numerous cilia and ciliary patterns, present on lateral horns, prostomium, and interramal papillae; unique paired ciliated patches on ventral side of body. Remarks . The genus Axiokebuita and type species, A. millsi were originally described from upper slope depths off Nova Scotia (Pocklington & Fournier, 1987). In the same paper, the authors referred Kebuita minuta Hartman (1967) from Antarctica to their new genus while at the same time referred some of the Antarctic specimens to A. millsi implying that the species was bipolar in distribution. Records of Axiokebuita are few; the literature was reviewed by Blake (2020). Parapar et al . (2011) examined specimens of A. minuta from Antarctica and among other things, referred the type-species, A. millsi to synonymy with A. minuta thus establishing the species as more or less cosmopolitan and bipolar in distribution. Unfortunately, these authors did ...